2023
DOI: 10.18502/jpc.v10i4.11581
|View full text |Cite
|
Sign up to set email alerts
|

Study of Drug Utilization Pattern during Second Wave of Covid-19 in a Tertiary Care Centre: A Retrospective Cross Sectional Study

Abstract: Background: To study the drug utilization trends among patients with COVID-19 disease during the second wave in a tertiary care hospital. Methods: A retrospective cross-sectional study was conducted in patients admitted in COVID-19 wards during second wave of SARS – COVID-19 pandemic from 1st March 2021 to 30th June 2021. A total of 300 prescriptions were analysed. Assessment of prescription patterns were done as per the WHO-The International Network for Rational Use of Drugs (INRUD)drug use indicators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Vaughn VM et al, suggested that prophylactic-and treatment-dose anticoagulation strategies are associated with lower in-hospital mortality 16 .COVID-19 was associated with inflammation and hypercoagulable states and in some studies elevation of coagulation markers were associated with worse clinical outcomes. Many studies have shown decreased incidence of COVID-19 complications after initiating anticoagulant therapy 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Vaughn VM et al, suggested that prophylactic-and treatment-dose anticoagulation strategies are associated with lower in-hospital mortality 16 .COVID-19 was associated with inflammation and hypercoagulable states and in some studies elevation of coagulation markers were associated with worse clinical outcomes. Many studies have shown decreased incidence of COVID-19 complications after initiating anticoagulant therapy 17 .…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 is an ongoing pandemic emergency disease; patients were treated according to symptoms and complications. There should not be any criteria for polypharmacy in this pandemic period [13]. The percentage of drugs prescribed from the essential drug list is 83.34%.…”
Section: Malek Et Almentioning
confidence: 99%
“…In disease outcome, deaths were reported in 55.74% of diabetics having COVID-19 compared to 44.26% of non-diabetics having COVID-19. Hence, the mortality rate increases up to 11.48% in diabetics [13].…”
Section: As Shown Inmentioning
confidence: 99%